Elastic properties of neck vessels in six-year-old children born with extremely low, very low and low body weight - A. I. Mulyukova; L. V. Yakovleva; Z. K. Galysheva; G. N. Shangareeva (Translational Medicine, 2026)
Background. The aim of the study was to investigate the elastic properties of the neck vessels in 6-year-old children born with extremely low (ELBW), very low (VLBW) and low body weight (LBW) as predictors of the development of cardiovascular diseases in subsequent years. Objective. To study the elastic properties of the neck vessels in 6-year-old children born with ELBW, VLBW, and LBW as predictors of the development of cardiovascular diseases in subsequent years. Materials and methods. The elastic properties of the neck vessels were assessed in 173 6-year-old children using echotraking. The children were divided into the following subgroups based on their birth weight: those born with extremely low (ELBW) (n=15), very low (VLBW) (n=25), low (LBW) (n=54), and a control group (n=79). The systolic and diastolic diameters of the vessel, the stiffness of the common carotid artery wall, and the compliance, distensibility, Peterson elasticity modulus, Young’s modulus, Gosling pulsatility index, and Purlot’s resistance index were determined based on the analysis of the coefficients. Results. In 6-yearold children who were born with extremely low, very low and low body weight, there were statistically significant changes in the elastic properties of the vascular wall of the common carotid arteries compared to the control group. The compliance coefficient and the extensibility coefficient of the common carotid artery were significantly lower in six-year-old children who were born with extremely low, very low and low body weight. At the same time, the resistance coefficient and the stiffness index of the common carotid artery in the studied groups of children were significantly higher than in the control group. The median thickness of the intima-media complex in the control group was statistically significantly lower than in the groups of children born with extremely low, very low and low body weight. Conclusion. The results obtained indicate early preclinical vascular changes in children with extremely low, very low and low body weight at birth and the possibility of using ultrasound studies in order to detect them.